Edukasi Pilah Sampah pada Masyarakat Desa Labuaja, Kabupaten Maros - Ekasari, Ranti; Syarfaini; Surahmawati (Sociality: Journal of Public Health Service, 2023)
Garbage is one of the environmental health problems in Indonesia. Household waste management requires the active involvement of individuals and community groups, in addition to the government’s role as a facilitator. Urban solid waste management requires active access by individuals and community groups, in addition to the role of government facilitators. One of the groups that should be given an understanding of the importance of protecting the environment by sorting waste is elementary school teachers. This service aims to provide increased knowledge about how to sort waste. The service method used is Asset Based Community Development (ABCD) at SDN 247 Pattiro, Labuaja Village, Maros Regency. The service was carried out on December 11, 2021 with a total of 56 students (i). The service was carried out by giving the pre-test questionnaire first, then providing counseling, then giving the post-test questionnaire again with the same questions. Data were analyzed using the dependent t-test. The results of the service show that there is an increase in students’ knowledge after education is given. It is suggested to the school to follow up on the waste sorting education that has been carried out so that the perceived benefits can be sustainable.